PENGGUNAAN MEDIA PEMBELAJARAN FLASH CARD DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA ANAK AUTISTIK KELAS VI SDLB DI SKh NEGERI 02 LEBAK - Ikma Nurohman; Dr. Hj. Isti Rusdiyani, M.Pd; Reza Febri Abadi, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
Abstract  The use of flash card media is used as a learning media for intervention because this media can stimulate children to want to learn to read and can stimulate an increase in the ability to read vowels and syllables of autistic children. The flash card media used in this study is a media created by researchers to improve the ability to read the beginning of a child. This study aims to determine the effectiveness of the use of flash card learning media on the ability to read the beginning of autistic children in class VI SDLB SKh 02 Lebak. This research is an experimental study with the approach of Single Subject Research (SSR). The research design used in this study uses a reversal design with the form of A-B-A. The data obtained were analyzed using descriptive statistics and displayed through line graphs. The subjects in this study focused on an autistic child in class VI SDLB with the initials MAH. The study was conducted for approximately one month with the number of research sessions which was 16 times with the target of the behavior of reading vowels and reading syllables. Based on the results of the study, it is known that the use of flash card learning media can improve the ability to read the beginning of autistic children in class VI SDLB SKh 02 Lebak. This is indicated by the increase in the average data acquisition on the two target behaviors. The results obtained from the target behavior 1 (vowel reading) in phase A1 (baseline 1) were 48.75%, after the intervention in phase (B) the average data obtained gained increased to 87.5%, and after giving it the intervention data obtained on phase A2 (baseline 2) was 73.75%. For target behavior 2 (reading syllables) the results of the average acquisition of data obtained in phase A1 (baseline 1) are 25%, after intervention in phase (B) the average data obtained obtained increases to 84%, and after given intervention the average data obtained in phase A2 (baseline 2) was 68%. Thus, it can be concluded that the use of flash card learning media effectively improves the ability to read the beginning of autistic children in class VI SDLB SKh 02 Lebak.